"The American Sentence". - Nadel, Ira (Canadian Review of American Studies, 2023)
The nature, history, and transformation of the American sentence in twentieth-century American fiction is the focus of this article, which examines the shift from the oracular to ordinary style, the contrast between James and Hemingway, or Thomas Wolfe and Cormac McCarthy. Examples of twentieth-century writers include Gertrude Stein, William Faulkner, J.D. Salinger, Thomas Pynchon, Cormac McCarthy, and Jennifer Eagan. Overlooked, the sentence remains the core of literary expression, but it is a problematic form associated with such cultural changes as the telegraph, World War II, and crime writing, as much as the literary imagination.